Análise espacial de uma transeção de solo agrícola cultivado com soja. - Oliveira, Marcio Paulo de (2010)
The knowledge about soil and plant attributes is important for the improvement of agricultural management. Intense tillage activities may induce not only alterations in the soil attributes but also decrease in productivity. Studies directed to the soil and plant spatial variability identification and the relations amid these variables are tools for agriculture, with the potential to increase productivity. The data set for this study was sampled in a Rhodic Acrudox soil, at a farmland that has been being cultivated for over five years under no-tillage system, with soybean and wheat in crop succession. At 252 m long transect, 84 points were demarcated, with 3 m of spacing between each of them. The relations between soybean productivity and soil water content, micro, macro and total porosity, soil density and soil resistance to penetration at 0,0-0,10 m and 0,10-0,20 m deep layers, were evaluated, as well as the respective variabilities. The relations between soybean productivity and soil attributes were determined using simple and cross correlations, followed by the state space models determinations, compared to linear and multiple regression models. The results have shown that the soybean productivity and soil mechanical resistance variables presented not only autocorrelation structure but also crosscorrelation structure. The state space models, relating to the soybean productivity at a point i, with the same attribute at point i-1, at the two layers, were more efficient than the equivalent models in simple and multiple regression. With geoestatistics, the spatial dependence structure was determined with envelopes and models for the semivariograms, allowing identification and classification of the spatial dependence for the variables under study. The thematic maps were obtained with simple kriging and indicated the soil attributes behavior, related to the soybean productivity.